Do Professional Athletes Perform Better Than Recreational Athletes After Arthroscopy for Femoroacetabular Impingement? - Malviya, Ajay (Springer US, 2013)
BACKGROUND: Although a large number of athletes’ returns to sports after hip arthroscopic surgery for femoroacetabular impingement (FAI), it is not clear if they do so to the preinjury level and whether professional athletes (PA) are more likely to return to the preinjury level compared with recreational athletes (RA). QUESTIONS/PURPOSES: We therefore compared (1) the time taken to return to the preinjury level of sport between professional and recreational athletes; (2) the degree of improvement in time spent in training and competitive activities after arthroscopic surgery for FAI; and (3) the difference in trend of improvement in hip scores. METHODS: We prospectively followed 80 athletes (PA = 40, RA = 40; mean age, 35.7 years; males = 50, females = 30; mean followup, 1.4 years; range, 1–1.8 years) who underwent hip arthroscopy for FAI. We measured the time to return to sports; training time and time in competition; and the modified Harris hip score and the nonarthritic hip score. RESULTS: There was a 2.6-fold improvement in the training time (from 7.8 to 20 hours per week) and a 3.2-fold increase in time in competition (from 2.5 to 7.9 hours per week) 1 year after surgery. The mean time to return to sporting activities was 5.4 months, which was lower for PA (4.2) as compared with RA (6.8). Eighty-two percent (66) (PA = 88% [35] versus RA = 73% [29]) returned to their preinjury level of sport within 1 year of surgery. CONCLUSIONS: The data suggest PA may show quicker return to sports than RA but the hip scores and rate of return to sports are similar. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.